The relevance of biochar and co-applied SynComs on maize quality and sustainability: Evidence from field experiments - Gullì, Mariolina; Cangioli, Lisa; Frusciante, Sarah; Graziano, Sara; Caldara, Marina; Fiore, Alessia; Klonowski, Alexandra M.; Maestri, Elena; Brunori, Andrea; Mengoni, Alessio; Pihlanto, Anne; Diretto, Gianfranco; et al. (Elsevier, 2025)
Adoption of sustainable maize cropping practices is urgently needed. Synthetic microbial communities (SynComs) made of plant growth-promoting microorganisms (PGPMs), coupled with biochar from residual biomass, offer an environmentally compatible alternative to inorganic fertilizers and may improve soil fertility. This article extends in a two-year field trial with preliminary results obtained in previous pot experiments, monitoring plant physiology, soil biology and chemistry, and kernel metabolomics. Here, we report the synergistic effect of the co-application of biochar, SynComs, and arbuscular mycorrhizal fungi on the soil microbiome, maize growth, and kernel metabolomic profile. SynComs application did not affect the diversity and richness of soil microbial communities; therefore, it posed a low risk of long-term effects on soil microbial ecology. With SynComs and biochar co-application to the soil, the physiology of maize plants was characterized by higher chlorophyll content, ear weight, and kernel weight. The combination of SynComs and biochar also affected the kernel metabolome, resulting in enriched health-beneficial and anti-stress metabolites. Since the preliminary evidence on the environmental and economic impact of these new associations was more favorable than that of conventional fertilizers, it seems reasonable that their large-scale implementation can eventually favor the transition to more sustainable agriculture.
Keywords: biochar; synthetic microbial consortia; sustainable agriculture; from field to fork